Origin of recognition complex 3 controls the development of maternal excess endosperm in the Paspalum simplex agamic complex ( Poaceae ) - Bellucci, Michele (2023)
Pseudogamous apomixis in Paspalum simplex generates seeds with embryos genetically identical to the mother plant and endosperms deviating from the canonical 2(maternal):1(paternal) parental genome contribution into a maternal excess 4m:1p genome ratio. In P. simplex the gene homologous to the one coding for the subunit 3 of the ORIGIN OF RECOGNITION COMPLEX (PsORC3) exists in three isogenic forms: PsORC3a is apomixis-specific and constitutively expressed in developing endosperm whereas PsORCb and PsORCc are up regulated in sexual endosperms and silenced in apomictic ones. This raises the question of how the different arrangement and expression profiles of these three ORC3 isogenes are linked to seed development in interploidy crosses generating maternal excess endosperms. We demonstrate that the PsORC3b downregulation in sexual tetraploid plants is sufficient to restore seed fertility in interploidy 4n x 2n crosses and, in turn, its expression level at the transition from proliferating to endoreduplication endosperm developmental stages dictates the fate of these seeds. Furthermore, we show that only when being maternally inherited, PsORC3c can up-regulate PsORC3b. Our findings lay the basis for an innovative route - based on ORC3 manipulation - to introgress the apomictic trait into sexual crops and overcome the fertilization barriers in interploidy crosses.